week11 tweaks
[lambda.git] / manipulating_trees_with_monads.mdwn
index d4b0bd8..d0897ef 100644 (file)
@@ -17,64 +17,58 @@ instance, in the way that the reader monad allowed us to add a layer
 of intensionality to an extensional grammar, but we have not yet seen
 the utility of replacing one monad with other.
 
-First, we'll be needing a lot of trees during the remainder of the
-course.  Here's a type constructor for binary trees:
+First, we'll be needing a lot of trees for the remainder of the
+course.  Here again is a type constructor for leaf-labeled, binary trees:
 
     type 'a tree = Leaf of 'a | Node of ('a tree * 'a tree)
 
-These are trees in which the internal nodes do not have labels.  [How
-would you adjust the type constructor to allow for labels on the
+[How would you adjust the type constructor to allow for labels on the
 internal nodes?]
 
 We'll be using trees where the nodes are integers, e.g.,
 
 
-<pre>
-let t1 = Node ((Node ((Leaf 2), (Leaf 3))),
-               (Node ((Leaf 5),(Node ((Leaf 7),
-                                      (Leaf 11))))))
-
-    .
- ___|___
- |     |
- .     .
-_|__  _|__
-|  |  |  |
-2  3  5  .
-        _|__
-        |  |
-        7  11
-</pre>
+       let t1 = Node (Node (Leaf 2, Leaf 3),
+                      Node (Leaf 5, Node (Leaf 7,
+                                             Leaf 11)))
+           .
+        ___|___
+        |     |
+        .     .
+       _|_   _|__
+       |  |  |  |
+       2  3  5  .
+               _|__
+               |  |
+               7  11
 
 Our first task will be to replace each leaf with its double:
 
-<pre>
-let rec treemap (newleaf:'a -> 'b) (t:'a tree):('b tree) =
-  match t with Leaf x -> Leaf (newleaf x)
-             | Node (l, r) -> Node ((treemap newleaf l),
-                                    (treemap newleaf r));;
-</pre>
-`treemap` takes a function that transforms old leaves into new leaves, 
+       let rec treemap (newleaf : 'a -> 'b) (t : 'a tree) : 'b tree =
+         match t with
+           | Leaf i -> Leaf (newleaf i)
+           | Node (l, r) -> Node (treemap newleaf l,
+                                  treemap newleaf r);;
+
+`treemap` takes a function that transforms old leaves into new leaves,
 and maps that function over all the leaves in the tree, leaving the
 structure of the tree unchanged.  For instance:
 
-<pre>
-let double i = i + i;;
-treemap double t1;;
-- : int tree =
-Node (Node (Leaf 4, Leaf 6), Node (Leaf 10, Node (Leaf 14, Leaf 22)))
-
-    .
- ___|____
- |      |
- .      .
-_|__  __|__
-|  |  |   |
-4  6  10  .
-        __|___
-        |    |
-        14   22
-</pre>
+       let double i = i + i;;
+       treemap double t1;;
+       - : int tree =
+       Node (Node (Leaf 4, Leaf 6), Node (Leaf 10, Node (Leaf 14, Leaf 22)))
+       
+           .
+        ___|____
+        |      |
+        .      .
+       _|__  __|__
+       |  |  |   |
+       4  6  10  .
+               __|___
+               |    |
+               14   22
 
 We could have built the doubling operation right into the `treemap`
 code.  However, because what to do to each leaf is a parameter, we can
@@ -82,184 +76,176 @@ decide to do something else to the leaves without needing to rewrite
 `treemap`.  For instance, we can easily square each leaf instead by
 supplying the appropriate `int -> int` operation in place of `double`:
 
-<pre>
-let square x = x * x;;
-treemap square t1;;
-- : int tree =ppp
-Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
-</pre>
+       let square i = i * i;;
+       treemap square t1;;
+       - : int tree =ppp
+       Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
 
 Note that what `treemap` does is take some global, contextual
 information---what to do to each leaf---and supplies that information
 to each subpart of the computation.  In other words, `treemap` has the
-behavior of a reader monad.  Let's make that explicit.  
+behavior of a reader monad.  Let's make that explicit.
 
 In general, we're on a journey of making our treemap function more and
-more flexible.  So the next step---combining the tree transducer with
+more flexible.  So the next step---combining the tree transformer with
 a reader monad---is to have the treemap function return a (monadized)
-tree that is ready to accept any `int->int` function and produce the
+tree that is ready to accept any `int -> int` function and produce the
 updated tree.
 
-\tree (. (. (f2) (f3))(. (f5) (.(f7)(f11))))
-<pre>
-\f    .
-  ____|____
-  |       |
-  .       .
-__|__   __|__
-|   |   |   |
-f2  f3  f5  .
-          __|___
-          |    |
-          f7  f11
-</pre>
+\tree (. (. (f 2) (f 3)) (. (f 5) (. (f 7) (f 11))))
+
+       \f      .
+          _____|____
+          |        |
+          .        .
+        __|___   __|___
+        |    |   |    |
+       f 2  f 3  f 5  .
+                    __|___
+                    |    |
+                   f 7  f 11
 
 That is, we want to transform the ordinary tree `t1` (of type `int
-tree`) into a reader object of type `(int->int)-> int tree`: something 
-that, when you apply it to an `int->int` function returns an `int
-tree` in which each leaf `x` has been replaced with `(f x)`.
+tree`) into a reader object of type `(int -> int) -> int tree`: something
+that, when you apply it to an `int -> int` function `f` returns an `int
+tree` in which each leaf `i` has been replaced with `f i`.
 
 With previous readers, we always knew which kind of environment to
 expect: either an assignment function (the original calculator
 simulation), a world (the intensionality monad), an integer (the
 Jacobson-inspired link monad), etc.  In this situation, it will be
 enough for now to expect that our reader will expect a function of
-type `int->int`.
+type `int -> int`.
 
-<pre>
-type 'a reader = (int->int) -> 'a;;  (* mnemonic: e for environment *)
-let reader_unit (x:'a): 'a reader = fun _ -> x;;
-let reader_bind (u: 'a reader) (f:'a -> 'c reader):'c reader = fun e -> f (u e) e;;
-</pre>
+       type 'a reader = (int -> int) -> 'a;;  (* mnemonic: e for environment *)
+       let reader_unit (a : 'a) : 'a reader = fun _ -> a;;
+       let reader_bind (u: 'a reader) (f : 'a -> 'b reader) : 'b reader = fun e -> f (u e) e;;
 
 It's easy to figure out how to turn an `int` into an `int reader`:
 
-<pre>
-let int2int_reader (x:'a): 'b reader = fun (op:'a -> 'b) -> op x;;
-int2int_reader 2 (fun i -> i + i);;
-- : int = 4
-</pre>
+       let int2int_reader : 'a -> 'b reader = fun (a : 'a) -> fun (op : 'a -> 'b) -> op a;;
+       int2int_reader 2 (fun i -> i + i);;
+       - : int = 4
 
 But what do we do when the integers are scattered over the leaves of a
 tree?  A binary tree is not the kind of thing that we can apply a
-function of type `int->int` to.
+function of type `int -> int` to.
 
-<pre>
-let rec treemonadizer (f:'a -> 'b reader) (t:'a tree):('b tree) reader =
-  match t with Leaf x -> reader_bind (f x) (fun x' -> reader_unit (Leaf x'))
-             | Node (l, r) -> reader_bind (treemonadizer f l) (fun x ->
-                                reader_bind (treemonadizer f r) (fun y ->
-                                  reader_unit (Node (x, y))));;
-</pre>
+       let rec treemonadizer (f : 'a -> 'b reader) (t : 'a tree) : 'b tree reader =
+           match t with
+           | Leaf i -> reader_bind (f i) (fun i' -> reader_unit (Leaf i'))
+           | Node (l, r) -> reader_bind (treemonadizer f l) (fun x ->
+                              reader_bind (treemonadizer f r) (fun y ->
+                                reader_unit (Node (x, y))));;
 
 This function says: give me a function `f` that knows how to turn
-something of type `'a` into an `'b reader`, and I'll show you how to 
-turn an `'a tree` into an `'a tree reader`.  In more fanciful terms, 
+something of type `'a` into an `'b reader`, and I'll show you how to
+turn an `'a tree` into an `'a tree reader`.  In more fanciful terms,
 the `treemonadizer` function builds plumbing that connects all of the
 leaves of a tree into one connected monadic network; it threads the
-monad through the leaves.
+`'b reader` monad through the leaves.
 
-<pre>
-# treemonadizer int2int_reader t1 (fun i -> i + i);;
-- : int tree =
-Node (Node (Leaf 4, Leaf 6), Node (Leaf 10, Node (Leaf 14, Leaf 22)))
-</pre>
+       # treemonadizer int2int_reader t1 (fun i -> i + i);;
+       - : int tree =
+       Node (Node (Leaf 4, Leaf 6), Node (Leaf 10, Node (Leaf 14, Leaf 22)))
 
 Here, our environment is the doubling function (`fun i -> i + i`).  If
 we apply the very same `int tree reader` (namely, `treemonadizer
-int2int_reader t1`) to a different `int->int` function---say, the
+int2int_reader t1`) to a different `int -> int` function---say, the
 squaring function, `fun i -> i * i`---we get an entirely different
 result:
 
-<pre>
-# treemonadizer int2int_reader t1 (fun i -> i * i);;
-- : int tree =
-Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
-</pre>
+       # treemonadizer int2int_reader t1 (fun i -> i * i);;
+       - : int tree =
+       Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
 
-Now that we have a tree transducer that accepts a monad as a
+Now that we have a tree transformer that accepts a reader monad as a
 parameter, we can see what it would take to swap in a different monad.
 For instance, we can use a state monad to count the number of nodes in
 the tree.
 
-<pre>
-type 'a state = int -> 'a * int;;
-let state_unit x i = (x, i+.5);;
-let state_bind u f i = let (a, i') = u i in f a (i'+.5);;
-</pre>
+       type 'a state = int -> 'a * int;;
+       let state_unit a = fun s -> (a, s);;
+       let state_bind_and_count u f = fun s -> let (a, s') = u s in f a (s' + 1);;
 
 Gratifyingly, we can use the `treemonadizer` function without any
 modification whatsoever, except for replacing the (parametric) type
-`reader` with `state`:
+`'b reader` with `'b state`, and substituting in the appropriate unit and bind:
 
-<pre>
-let rec treemonadizer (f:'a -> 'b state) (t:'a tree):('b tree) state =
-  match t with Leaf x -> state_bind (f x) (fun x' -> state_unit (Leaf x'))
-             | Node (l, r) -> state_bind (treemonadizer f l) (fun x ->
-                                state_bind (treemonadizer f r) (fun y ->
-                                  state_unit (Node (x, y))));;
-</pre>
+       let rec treemonadizer (f : 'a -> 'b state) (t : 'a tree) : 'b tree state =
+           match t with
+           | Leaf i -> state_bind_and_count (f i) (fun i' -> state_unit (Leaf i'))
+           | Node (l, r) -> state_bind_and_count (treemonadizer f l) (fun x ->
+                              state_bind_and_count (treemonadizer f r) (fun y ->
+                                state_unit (Node (x, y))));;
 
 Then we can count the number of nodes in the tree:
 
-<pre>
-# treemonadizer state_unit t1 0;;
-- : int tree * int =
-(Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11))), 13)
-
-    .
- ___|___
- |     |
- .     .
-_|__  _|__
-|  |  |  |
-2  3  5  .
-        _|__
-        |  |
-        7  11
-</pre>
+       # treemonadizer state_unit t1 0;;
+       - : int tree * int =
+       (Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11))), 13)
+       
+           .
+        ___|___
+        |     |
+        .     .
+       _|__  _|__
+       |  |  |  |
+       2  3  5  .
+               _|__
+               |  |
+               7  11
 
 Notice that we've counted each internal node twice---it's a good
 exercise to adjust the code to count each node once.
 
+<!--
+A tree with n leaves has 2n - 1 nodes.
+This function will currently return n*1 + (n-1)*2 = 3n - 2.
+To convert b = 3n - 2 into 2n - 1, we can use: let n = (b + 2)/3 in 2*n -1
+
+But I assume Chris means here, adjust the code so that no corrections of this sort have to be applied.
+-->
+
+
 One more revealing example before getting down to business: replacing
 `state` everywhere in `treemonadizer` with `list` gives us
 
-<pre>
-# treemonadizer (fun x -> [ [x; square x] ]) t1;;
-- : int list tree list =
-[Node
-  (Node (Leaf [2; 4], Leaf [3; 9]),
-   Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))]
-</pre>
+       # treemonadizer (fun i -> [ [i; square i] ]) t1;;
+       - : int list tree list =
+       [Node
+         (Node (Leaf [2; 4], Leaf [3; 9]),
+          Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))]
 
 Unlike the previous cases, instead of turning a tree into a function
 from some input to a result, this transformer replaces each `int` with
 a list of `int`'s.
 
-Now for the main point.  What if we wanted to convert a tree to a list
-of leaves?  
+<!--
+We don't make it clear why the fun has to be int -> int list list, instead of int -> int list
+-->
 
-<pre>
-type ('a, 'r) continuation = ('a -> 'r) -> 'r;;
-let continuation_unit x c = c x;;
-let continuation_bind u f c = u (fun a -> f a c);;
 
-let rec treemonadizer (f:'a -> ('b, 'r) continuation) (t:'a tree):(('b tree), 'r) continuation =
-  match t with Leaf x -> continuation_bind (f x) (fun x' -> continuation_unit (Leaf x'))
-             | Node (l, r) -> continuation_bind (treemonadizer f l) (fun x ->
-                                continuation_bind (treemonadizer f r) (fun y ->
-                                  continuation_unit (Node (x, y))));;
-</pre>
+Now for the main point.  What if we wanted to convert a tree to a list
+of leaves?
+
+       type ('a, 'r) continuation = ('a -> 'r) -> 'r;;
+       let continuation_unit a = fun k -> k a;;
+       let continuation_bind u f = fun k -> u (fun a -> f a k);;
+       
+       let rec treemonadizer (f : 'a -> ('b, 'r) continuation) (t : 'a tree) : ('b tree, 'r) continuation =
+           match t with
+           | Leaf i -> continuation_bind (f i) (fun i' -> continuation_unit (Leaf i'))
+           | Node (l, r) -> continuation_bind (treemonadizer f l) (fun x ->
+                              continuation_bind (treemonadizer f r) (fun y ->
+                                continuation_unit (Node (x, y))));;
 
 We use the continuation monad described above, and insert the
 `continuation` type in the appropriate place in the `treemonadizer` code.
 We then compute:
 
-<pre>
-# treemonadizer (fun a c -> a :: (c a)) t1 (fun t -> []);;
-- : int list = [2; 3; 5; 7; 11]
-</pre>
+       # treemonadizer (fun a k -> a :: (k a)) t1 (fun t -> []);;
+       - : int list = [2; 3; 5; 7; 11]
 
 We have found a way of collapsing a tree into a list of its leaves.
 
@@ -269,37 +255,33 @@ note that an interestingly uninteresting thing happens if we use the
 continuation unit as our first argument to `treemonadizer`, and then
 apply the result to the identity function:
 
-<pre>
-# treemonadizer continuation_unit t1 (fun x -> x);;
-- : int tree =
-Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11)))
-</pre>
+       # treemonadizer continuation_unit t1 (fun i -> i);;
+       - : int tree =
+       Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11)))
 
 That is, nothing happens.  But we can begin to substitute more
 interesting functions for the first argument of `treemonadizer`:
 
-<pre>
-(* Simulating the tree reader: distributing a operation over the leaves *)
-# treemonadizer (fun a c -> c (square a)) t1 (fun x -> x);;
-- : int tree =
-Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
+       (* Simulating the tree reader: distributing a operation over the leaves *)
+       # treemonadizer (fun a k -> k (square a)) t1 (fun i -> i);;
+       - : int tree =
+       Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
 
-(* Simulating the int list tree list *)
-# treemonadizer (fun a c -> c [a; square a]) t1 (fun x -> x);;
-- : int list tree =
-Node
- (Node (Leaf [2; 4], Leaf [3; 9]),
-  Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))
+       (* Simulating the int list tree list *)
+       # treemonadizer (fun a k -> k [a; square a]) t1 (fun i -> i);;
+       - : int list tree =
+       Node
       (Node (Leaf [2; 4], Leaf [3; 9]),
+         Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))
 
-(* Counting leaves *)
-# treemonadizer (fun a c -> 1 + c a) t1 (fun x -> 0);;
-- : int = 5
-</pre>
+       (* Counting leaves *)
+       # treemonadizer (fun a k -> 1 + k a) t1 (fun i -> 0);;
+       - : int = 5
 
 We could simulate the tree state example too, but it would require
-generalizing the type of the continuation monad to 
+generalizing the type of the continuation monad to
 
-    type ('a -> 'b -> 'c) continuation = ('a -> 'b) -> 'c;;
+       type ('a, 'b, 'c) continuation = ('a -> 'b) -> 'c;;
 
 The binary tree monad
 ---------------------
@@ -307,79 +289,74 @@ The binary tree monad
 Of course, by now you may have realized that we have discovered a new
 monad, the binary tree monad:
 
-<pre>
-type 'a tree = Leaf of 'a | Node of ('a tree) * ('a tree);;
-let tree_unit (x:'a) = Leaf x;;
-let rec tree_bind (u:'a tree) (f:'a -> 'b tree):'b tree = 
-  match u with Leaf x -> f x 
-             | Node (l, r) -> Node ((tree_bind l f), (tree_bind r f));;
-</pre>
+       type 'a tree = Leaf of 'a | Node of ('a tree) * ('a tree);;
+       let tree_unit (a: 'a) = Leaf a;;
+       let rec tree_bind (u : 'a tree) (f : 'a -> 'b tree) : 'b tree =
+           match u with
+           | Leaf a -> f a
+           | Node (l, r) -> Node ((tree_bind l f), (tree_bind r f));;
 
 For once, let's check the Monad laws.  The left identity law is easy:
 
-    Left identity: bind (unit a) f = bind (Leaf a) f = fa
+    Left identity: bind (unit a) f = bind (Leaf a) f = f a
 
 To check the other two laws, we need to make the following
 observation: it is easy to prove based on `tree_bind` by a simple
 induction on the structure of the first argument that the tree
 resulting from `bind u f` is a tree with the same strucure as `u`,
-except that each leaf `a` has been replaced with `fa`:
-
-\tree (. (fa1) (. (. (. (fa2)(fa3)) (fa4)) (fa5)))
-<pre>
-                .                         .       
-              __|__                     __|__   
-              |   |                     |   |   
-              a1  .                    fa1  .   
-                 _|__                     __|__ 
-                 |  |                     |   | 
-                 .  a5                    .  fa5
-   bind         _|__       f   =        __|__   
-                |  |                    |   |   
-                .  a4                   .  fa4  
-              __|__                   __|___   
-              |   |                   |    |   
-              a2  a3                 fa2  fa3         
-</pre>   
+except that each leaf `a` has been replaced with `f a`:
+
+\tree (. (f a1) (. (. (. (f a2) (f a3)) (f a4)) (f a5)))
+
+                       .                         .
+                     __|__                     __|__
+                     |   |                     |   |
+                     a1  .                   f a1  .
+                        _|__                     __|__
+                        |  |                     |   |
+                        .  a5                    .  f a5
+          bind         _|__       f   =        __|__
+                       |  |                    |   |
+                       .  a4                   .  f a4
+                     __|__                   __|___
+                     |   |                   |    |
+                     a2  a3                f a2  f a3
 
 Given this equivalence, the right identity law
 
-    Right identity: bind u unit = u
+       Right identity: bind u unit = u
 
 falls out once we realize that
 
-    bind (Leaf a) unit = unit a = Leaf a
+       bind (Leaf a) unit = unit a = Leaf a
 
 As for the associative law,
 
-    Associativity: bind (bind u f) g = bind u (\a. bind (fa) g)
+       Associativity: bind (bind u f) g = bind u (\a. bind (fa) g)
 
 we'll give an example that will show how an inductive proof would
 proceed.  Let `f a = Node (Leaf a, Leaf a)`.  Then
 
-\tree (. (. (. (. (a1)(a2)))))
-\tree (. (. (. (. (a1) (a1)) (. (a1) (a1)))  ))
-<pre>
-                                           .
-                                       ____|____
-          .               .            |       |
-bind    __|__   f  =    __|_    =      .       .
-        |   |           |   |        __|__   __|__
-        a1  a2         fa1 fa2       |   |   |   |
-                                     a1  a1  a1  a1  
-</pre>
+\tree (. (. (. (. (a1) (a2)))))
+\tree (. (. (. (. (a1) (a1)) (. (a1) (a1)))))
+
+                                                  .
+                                              ____|____
+                 .               .            |       |
+       bind    __|__   f  =    __|_    =      .       .
+               |   |           |   |        __|__   __|__
+               a1  a2        f a1 f a2      |   |   |   |
+                                            a1  a1  a1  a1
 
 Now when we bind this tree to `g`, we get
 
-<pre>
-           .
-       ____|____
-       |       |
-       .       .
-     __|__   __|__
-     |   |   |   |
-    ga1 ga1 ga1 ga1  
-</pre>
+                   .
+              _____|______
+              |          |
+              .          .
+            __|__      __|__
+            |   |      |   |
+          g a1 g a1  g a1 g a1
 
 At this point, it should be easy to convince yourself that
 using the recipe on the right hand side of the associative law will
@@ -390,6 +367,5 @@ So binary trees are a monad.
 Haskell combines this monad with the Option monad to provide a monad
 called a
 [SearchTree](http://hackage.haskell.org/packages/archive/tree-monad/0.2.1/doc/html/src/Control-Monad-SearchTree.html#SearchTree)
-that is intended to 
-represent non-deterministic computations as a tree.
+that is intended to represent non-deterministic computations as a tree.